The mediating effect of role conflict and role ambiguity on faculty’s job satisfaction and commitment - Homayed, Assil (2020)
Purpose: The primary purpose of this study was to explore the mediating effect of role conflict and role ambiguity on faculty’s job satisfaction and commitment since minimal research has been done from this aspect on faculty members. It also aimed at finding if a direct relationship exists between faculty’s job satisfaction and commitment and investigate the relationship among the variables when role conflict and role ambiguity were introduced as mediators. Faculty members of a top institution of higher education in Lebanon were chosen as a sample of the study. Design/methodology/approach: Quantitative analysis was conducted in this study where surveys were distributed and collected. The sample of the study included the full time and part time faculty members of a prominent university in Lebanon. The data obtained from 133 participants were analyzed using the Rstudio software and the hypothetical model was tested using structural equation modeling through Onyx. Findings: The findings of the researcher resulted in a new version of organizational commitment scale where normative commitment scale was dropped, and continuance commitment scale was divided into two subscales. It was demonstrated that the updated commitment is more applicable to faculty members. The results supported H1a (There is a direct relationship between JS and AC); and H1b (There is a direct relationship between JS and Alt CC); whereas H1c was not supported (There is a direct relationship between JS and CC Econ). H2 was supported (Role ambiguity mediates the relationship between job satisfaction and organizational commitment), as RA partially mediated the relationship between JS and AC, fully mediated the relationship between JS and CC Econ, and also served as a mediator between JS and Alt CC. H3 was supported in the case of AC and Alt CC as RC partially mediated the relationship between JS and complete mediated the relationship between JS and Alt CC. However, RC had no mediative power in the relationship with CC Econ. Originality/value: This study highlights the importance of acknowledging and minimizing role conflict and role ambiguity in a workplace to result in a higher level of satisfaction and commitment among employees. It also gives an insight on understanding the relationship between job satisfaction and commitment among faculty members, in the case where role conflict and role ambiguity serve as a mediators. This paper adds value to the literature gap as a limited research exists on this topic and a new version of the organizational commitment scale was also developed, which is more relevant to faculty members.